Heterostructured calcium carbonate nanowires controlled by a cationic polyelectrolyte. Issue 5 (2nd January 2015) - Zhu, Jianhua; Huang, Lei; Cui, Mingfang; Ma, Li
Abstract : We are the first to report the heterostructures of aragonite nanowires on calcite crystals, and aragonite nanopillars decorated with rhombohedral calcite tips in a cationic polyelectrolyte mineral solution. Polymorph switching in the same structures attributes to spontaneous variations of the solutes in bulk solution and spatial distribution of the polymer in the microenvironment. Abstract : The heterostructured biomimetic materials of calcite microcrystals covered with aragonite nanowires, as well as aragonite fibers decorated with small calcite tips, were first synthesized in a cationic polyelectrolyte mineral solution. The polymorph switching in the same microstructures shows the close relationship with thermodynamic and kinetic reaction control.